Rainfall variability patterns in Nigeria during the rainy season - Chibuike Chiedozie Ibebuchi; Itohan-Osa Abu (Scientific Reports, 2023)
Abstract To enhance the physical understanding of the circulation patterns associated with rainfall variations in Nigeria, we spatially decomposed rainfall during the rainy season and uncovered the asymmetric atmospheric circulation patterns driving wet and dry regimes in specific parts of Nigeria. Also, we examined linear trends in rainfall and the circulation patterns driving the trends. Our result shows that during the analysis period (1979–2022), northern part of Nigeria has coherent rainfall anomaly that is coupled with rainfall variations over the Sahel (Pearson correlation coefficient (r) is 0.55), and sea surface temperature anomalies (SSTa) in the global oceans (r =  $$\left|0.5\right|$$ 0.5 ). The negative phases of the Pacific Decadal Oscillation, North Atlantic Oscillation, and the North Pacific Oscillation; and the positive phases of the Atlantic Multidecadal Oscillation and the Pacific warm pool are associated with rainfall increase over the northern part of Nigeria. Owing to the increasing trend in SSTa over the Mediterranean and the adjacent oceans, implying the weakening of dry northerly winds penetrating northern Nigeria, the rainfall trend is significantly positive in the northern part of Nigeria during the rainy season—with an increase of about 2–4 mm/year, especially during August. The circulation patterns associated with rainfall formation at the western and southeastern parts of Nigeria are shown to be associated with SSTa over the tropical Atlantic Ocean, south coast of Nigeria (r =  $$\left|0.4\right|$$ 0.4 ). Moreover, rainfall shows a negative trend, with a decrease of about 5 mm/year, in the southeastern parts of Nigeria, which can be linked to the warming trend over the Gulf of Guinea.